Evidence for the effectiveness of an oleo-resin capsicum aerosol as a repellent against wild elephants in Zimbabwe - Ferrel Osborn; L. Rasmussen (Pachyderm)
Test results from studies with free ranging elephants suggest a Capsicum-based aerosol solution has validity as an elephant repellent over both short (20-30m) and intermediate (20-30m) ranges, and that Capsicum is a short-term repellent. Preliminary results suggest that this chemical may act as a practical elephant deterrent which can be combined with aversive conditioning of problem elephants.